Contract for sale of patent rights to a petroleum apparatus - Perkins, James, active 1865.; Burnet, William H.
Bound holograph contract for sale of the patent rights to an improved apparatus designed and patented by James Perkins and William H. Burnet for refining and distilling petroleum. Sold to Daniel F. Tompkins primarily in exchange for shares in a company to be formed for employing the device. Document, executed in Newark, N.J., on April 5, 1865, includes a diagram of the machine.
Collection material in English.
Keywords: Tompkins, Daniel F; Distillation apparatus; Petroleum -- Refining; Petroleum industry and trade; Newark (N.J.) -- Commerce